Characterizations of cis-pinonic acid and n-fatty acids on fine aerosols in the Lower Fraser Valley during Pacific 2001 Air Quality Study - Y. Cheng; Li, S. M.; Leithead, A.; Brickell, P. C.; Leaitch, W. R. (ATMOSPHERIC ENVIRONMENT, 2004)
In order to characterize sources of fine carbonaceous aerosols, PM2.5 aerosols were sampled at 5 sites in forest, tunnel, urban, rural., and forest/urban areas in the Lower Fraser Valley (LFV) during the Pacific 2001 Air Quality Study. All sample filters were analyzed for cis-pinonic acid and n-fatty acids. cis-Pinonic acid varied from 0.6-46.5 ng m(-3) at the sites in the forest, rural and forest/urban mixing area, and was low, from < detection limit to 6.5 ng m(-3) at the tunnel and 0.3 to 20.4 ng m(-3) at the urban site. It showed consistent day-night differences at all locations, and was linearly correlated with alpha-pinene in forest areas. At the elevated mixing forest/urban site, the day-night pattern showed evidence of nighttime source of the acid. Straight-chain n-fatty acids on the aerosols showed evidence of the light-duty automobile source at the tunnel, with the highest concentration of all sites and a carbon number distribution with low CPI values. In the forest, the acids were the second highest of all sites, and the CPI value for the acids was the highest of all sites, indicating direct forest emissions. At other locations the n-fatty acids showed impacts from these sources, judging from the carbon number distributions. At the urban sites, there was evidence of meat cooking emissions contribution to the n-fatty acids. It was found that unsaturated n-fatty acids may be used as an indicator of the apparent ``age'' of the acids in aerosols, and that a photochemical half-life of 5 h was derived based on the comparison of the day and nighttime C-18:1/C-18:0 ratios at the sites. (C) 2004 Elsevier Ltd. All rights reserved.